Abu-Sahl al-Masihi (died circa 1010 AD): The Persian physician in the early medieval era. (August 2020) - Taghavi-Shirazi, Maryam; Ghods, Roshanak; Hashem-Dabaghian, Fataneh; Zargaran, Arman
In the early medieval era, in the time which is called the Islamic Golden Age, medicine flourished through the practice of Persian physicians (9th to 12th century AD). Abu-Sahl al-Masihi (died circa 1010 AD) was one of the physicians in that period who had great influence on the progress of medicine by his own writings as well as his influence on great scholars like Biruni and Avicenna as their teacher. He was a polymath and had many writings in various fields of science, in particular medical sciences. Some of his manuscripts in medicine were Al-Mia fil-Tibb (Book of the Hundred), Kitab al-Teb al-Koli (The General Medicine), Ezhar al-Hekmat Allah Ta'ala fi Khalgh al-Ensan (God's Mystery on the Creation of Man), Resalat al-Adwiya (Treatise of Drugs), Osool Elm Nabz (the Principles of Pulse), and Resala f ī Taḥqiq Amral-Wabaʾ (On the determination of the matter of infectious diseases). As a sign of his impact in Persian medicine, many later physicians (until 19th century) referred to and cited his works in their manuscripts several times.